Zakat and Mental Health: A Reflection on Islamic Values in Modern Life - Mu’allimah Rodhiyana; Rohimah Rohimah; Neneng Munajah; Hadi Yasin (International Journal of Zakat, 2025)
Zakat, as one of the five pillars of Islam, carries profound implications not only for economic justice but also for mental and spiritual well-being. This paper explores the interconnection between zakat and mental health through the lens of Islamic values in modern society. Using a qualitative descriptive approach and library research method, data were gathered from Qur’anic verses, hadith, classical fiqh literature, and contemporary journal articles related to Islamic psychology, spirituality, and social welfare. Thematic analysis was employed to identify how zakat contributes to psychological stability, emotional resilience, and social harmony. The findings reveal that zakat functions as both a spiritual and psychosocial mechanism. For muzakki (zakat givers), it purifies the soul from greed, nurtures gratitude, and fosters happiness through altruistic behavior. For mustahik (zakat recipients), it alleviates economic stress, restores dignity, and strengthens hope — all of which are essential components of mental health. Furthermore, zakat builds social solidarity and reduces feelings of isolation by promoting empathy and collective responsibility. The study concludes that zakat reflects a holistic model of well-being that integrates faith, emotion, and social ethics, providing a sustainable framework for mental health promotion in Muslim communities. When managed effectively, zakat institutions such as BAZNAS can serve as faith-based mental health systems that support both individual and societal resilience in facing modern psychological challenges.